Construction of the Khilafah State According to Taqiyuddin An-Nabhani: Foundation for Development of Perception Measurement Instruments about the Khilafah - Subando, Joko; Wibowo, Muhammad Kurniawan Budi (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
Measuring perceptions of the khilafah is crucial to answer the differences in research results that are currently developing. However, to obtain reliable research results requires valid and reliable measurement instruments, while valid instruments can only be obtained from precise measurement constructs. This study aims to describe the construction of the caliphate state according to Taqiyuddin An Nabhani in the perspective of modern state theory. Research using a historical approach, data obtained from primary sources in the form of books written by Taqiyuddin An Nabhani such as Nidzamul Islam, Nidzmul Hukmi fil islam, and secondary sources in the form of books by his students such as democracy kufur system written by Abdul Qadim Zallum. According to Taqiyuddin An Nabhani, the caliphate is a general leadership that applies islamic law and charges it across the country. The Caliphate was established to realize sharia maqasid by imposing sanctions and criminal penalties according to Islamic law, the form of a unitary state, the form of government of the caliphate. In a caliphate state sovereignty is in the hands of God (Allah Swt) while power is in the hands of the people. Constitution in general life that all citizens both Muslim and non-Muslim get equal rights, whereas in private life such as worship, marriage, food and clothing are left to their respective religions. Pengukuran persepsi tentang khilafah menjadi hal penting untuk menjawab perbedaan hasil penelitian yang saat ini berkembang. Namun untuk mendapatkan hasil penelitian yang dapat dipercaya membutuhkan instrumen pengukuran yang valid dan reliabel, sedangkan instrumen yang valid hanya dapat diperoleh dari konstruk pengukuran yang tepat. Penelitian ini bertujuan untuk mendeskripsikan konstruksi negara khilafah menurut Taqiyuddin An Nabhani dalam perspektif teori negara modern. Penelitian menggunakan metode penelitian sejarah dengan langkah pertama pengumpulan data terkait pemikiran negara Khilafah menurut Taqiyuddin An Nabhani (heuristics), kedua verifikasi data (source criticism), ketiga sintesis dan analisis, keempat penjelasan konstruk negara khilafah menurut Taqiyuddin An nabhani dalam perspektif teori negara modern. Menurut Taqiyuddin An Nabhani, khilafah adalah kepemimpinan umum yang menerapkan hukum islam dan mendakwahkannya ke penjuru negeri. Khilafah didirikan untuk mewujudkan maqasid syariah dengan memberlakukan sanksi dan pidana sesuai hukum Islam, bentuk negara kesatuan, bentuk pemerintahan khilafah. Dalam negara khilafah kedaulatan di tangan Asy Syari’ (Allah Swt) sedangkan kekuasaan di tangan umat. Konstitusi pada kehidupan umum bahwa semua warga negara baik muslim maupun non-muslim mendapatkan hak yang sama, sedangkan dalam kehidupan privat seperti peribadatan, pernikahan, makanan dan pakaian diserahkan kepada agama masing-masing. Hasil penelitian ini dapat digunakan sebagai fondasi dalam pengembangan instrumen pengukuran persepsi tentang khilafah